Organocatalytic enantioselective synthesis of double S-shaped quadruple helicene-like molecules - Shengli Huang; Haojun Wen; Yige Li; Wenling Qin; Pengfei Wang; Yu Lan; Shiqi Jia; Hailong Yan (Nature Communications)
Abstract Helicene-shaped molecules are compelling chemical structures with unique twisted helical chirality and remarkable properties. Although progress occurs in the catalytic asymmetric synthesis of helicene (-like) molecules, the enantioselective synthesis of multiple helicenes, especially four or higher helicity, is still challenging and has yet to be achieved. Herein, we report an organocatalytic [4 + 2] cycloadditions to achieve double S-shaped quadruple helicene-like molecules with high enantioselectivity (up to 96% e.e.). The enantioselective synthesis of (P,P,P,P) and (M,M,M,M) configurational quadruple helical molecules can be achieved by modulating the structure of the catalyst. Density functional theory (DFT) calculations show that the reaction involves the formation of a duplex vinylidene ortho-quinone methide (VQM) intermediate and two successive cycloaddition reactions. Configurational stability studies elucidate the isomerization process between the isomers. In addition, the structural features and optical properties of the quadruple helicene-like molecules were investigated to explore their potential applications.